The Realization of Islamic Politics of the Dutch East Indies Governmentand Its Effect on Islam (XIX-XX Century) - Samsul Bahri Hasibuan; Asep Achmad Hidayat; Usman Supendi (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
In the era of Dutch colonialism in the XIX-XX centuries, the political legal policies applied had the aim of maintaining imperialism in Indonesia by abolishing Islamic law and prioritizing customary and Western law. This paper aims to find out the realization of Islamic politics in the Dutch administration and its influence on Islam. This research uses the historical method which consists of four stages, namely: heuristics, criticism, interpretation and historiography. Based on the results of the study, it is concluded that there are three pillars of Snouck Hurgronje's Islamic politics used by the Dutch government when expanding Indonesia, namely; 1) religious field, 2) social and community fields, 3) politics. In realizing this Islamic politics, the Dutch initially gave space to Muslims in applying their teachings. Then, gradually the Dutch politicized Muslim law to help the colonization process. Various methods were carried out such as making it difficult for Muslims to perform the hajj pilgrimage, conducting teacher ordinances and supervision ordinances for Islamic education and anticipating all Muslim activities that were indicated by fanatical movements such as Pan Islam and Tarekat.